Lectora Inspire Interactive Media Based on Android on Class VI Elementary School Proclamation Event Material - Prihantara, Usman Bayu; Farid Ahmadi (MIMBAR PGSD Undiksha, 2023)
Students' opinions regarding the content of social studies learning regarding the meaning of the Proclamation of Independence are prosaic learning content, and the lack of learning models presented to teachers is less interesting. The frequent use of reading-only methods is also an obstacle in delivering material to students. It is what triggers low student learning outcomes. This research aims to develop Android-based Lectora Inspire media on the meaning of the Proclamation of Independence, as well as the influence of student learning outcomes in Class VI elementary schools. This type of research is developed using the ADDIE model. The methods used to collect data are observation, interviews, tests, and questionnaires. Data collection instruments use questionnaires and test questions. The subjects used in this research were teachers, students, learning media experts and learning material experts. Data analysis techniques use descriptive quantitative, qualitative and inferential statistics. The results obtained from this research were that students tested in large groups 84%, small groups 90%, teacher trials 96%, media expert tests 76%, material expert tests 95%, as well as the results of effectiveness tests through pretest and post-test which had a significant increase from small groups to large groups. It was concluded that the Android-based Lectora Inspire media on the meaning of the Proclamation of Independence was very good to use, effective, and very suitable for use in the learning process and also improved student learning outcomes.